Dietary Antioxidant Vitamins and Minerals and Breast Cancer Risk: Prospective Results from the SUN Cohort - Cesar I. Fernandez-Lazaro; Miguel Ángel Martínez-González; Inmaculada Aguilera-Buenosvinos; Alfredo Gea; Miguel Ruiz-Canela; Andrea Romanos-Nanclares; Estefanía Toledo (MDPI AG, 2021)
There is growing interest in natural antioxidants and their potential effects on breast cancer (BC). Epidemiological evidence, however, is inconsistent. We prospectively evaluated the association between dietary intake of vitamins A, C, and E, selenium, and zinc and BC among 9983 female participants from the SUN Project, a Mediterranean cohort of university graduates. Participants completed a food frequency questionnaire at baseline, and biennial follow-up information about incident BC diagnosis was collected. Cases were ascertained through revision of medical charts and consultation of the National Death Index. Cox proportional hazards models were used to estimate multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CI). During an average follow-up of 11.3 years, 107 incident BC cases were confirmed. The multivariable HRs (95% CI) for BC comparing extreme tertiles of energy-adjusted dietary intakes were 1.07 (0.64-1.77; Ptrend = 0.673) for vitamin A, 1.00 (0.58-1.71; Ptrend = 0.846) for vitamin C, 0.92 (0.55-1.54; Ptrend = 0.728) for vitamin E, 1.37 (0.85-2.20; Ptrend = 0.135) for selenium, and 1.01 (0.61-1.69; Ptrend = 0.939) for zinc. Stratified analyses showed an inverse association between vitamin E intake and postmenopausal BC (HRT3 vs. T1 = 0.35; 95% CI, 0.14-0.86; Ptrend = 0.027). Our results did not suggest significant protective associations between dietary vitamins A, C, and E, selenium, or zinc and BC risk.